TRACING AMERICAN SPIRIT IN INDONESIA’S INDEPENDENCE: A HISTORICAL-COMPARATIVE STUDY - Pasha, Nariza Ayu (Rubikon : Journal of Transnational American Studies, 2024)
The US and Indonesia, two countries that fought for freedom, are fascinating subjects to delve more into, despite their great distance from one another and their distant times of conflict. This research used a Transnational American Studies perspective and comparative-historical analysis. By using comparative historical analysis, this research aimed to explore the similarities and differences that exist in the journey of American independence and Indonesian independence. The results of this research showed that even though the independence movements in the US and Indonesia occurred several centuries apart, they had the same goal, namely opposing colonialism. Both showed the same enthusiasm to fight colonial power and the desire to determine the fate of their nation without interference from other parties. Thomas Paine and Bung Tomo through their writings and speeches led the spirit of independence in the US and Indonesia. Even though they use different communication styles, both have an impact in forming the spirit of resistance and unity of their nation. Additionally, by looking at the history of the struggle of the Indonesian people, it can be seen the spirit of freedom that the US promoted.